Α‐Chitin dissolution, N‐deacetylation and valorization in deep eutectic solvents. Issue 5 (12th March 2020) - Vicente, Filipa A.; Bradić, Bojana; Novak, Uroš; Likozar, Blaž
Abstract: Chitin displays a highly rigid structure due to the vast intra‐ and intermolecular hydrogen bonding, thus hindering its dissolution and deacetylation using most solvents. Deep eutectic solvents (DESs) are special and environmentally friendly solvents composed of a hydrogen bond acceptor and a hydrogen bond donor. This allows them to dissolve chitin by disturbing its natural hydrogen bonding while establishing new bonds, hence turning the polymer more susceptible to solvents. Therefore, four distinct DESs (choline chloride‐lactic acid ([Ch]Cl:LA), choline chloride:oxalic acid ([Ch]Cl:OA), choline chloride:urea ([Ch]Cl:U) and betaine‐glycerol (Bet:G)) were applied in chitin dissolution, being the most performant ones further applied in its homogenous N‐deacetylation with NaOH. In this work, a milder and more biocompatible approach was carried out by using 30 wt% NaOH at 80°C, instead of the typical ≥40 wt% NaOH at temperatures ≥100°C. Herein, the reaction process took up to 18 hours, being the results analyzed through ATR‐FTIR. Chitin was converted into chitosan with a 70‐80% degree of deacetylation (DDA) in a short period while using homogenous conditions. These promising results provide the first proof of concept of the ability of Bet:G and [Ch]Cl:LA‐based DESs to be used as a greener approach for the chitin homogeneous N‐deacetylation. Abstract :